Influencia del mantenimiento preventivo y correctivo de la infraestructura tecnológica para mejorar el proceso de enseñanza aprendizaje en la Escuela Patricia Chérrez, de la ciudad de Santa Rosa periodo lecitvo 2012-2013. - Balcázar Sánchez, Carlos Arturo (2013)
Today is innovating the integration of new technological resource, so the correct handling of them in order to improve educational processes, and thus generate significant learning in students using appropriate methods and techniques.